Morphosyntax of the Noun Phrase in Hieroglyphic Luwian. - Bauer, Anna (Brill's studies in Indo-European languages & linguistics., 2014)
In this book, Anna H. Bauer provides a full and detailed analysis of the noun phrases found in the Hieroglyphic Luwian corpus.